AB0740 Evaluation of hand dermal thickness and peripheral blood perfusion in systemic sclerosispatients. (12th June 2018) - Ruaro, B.; Sulli, A.; Santiago, T.; Pereira da Silva, J.A.; Pizzorni, C.; Tomatis, V.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is characterised by progressive skin involvement. The modified Rodnan Skin Score (mRSS) is the gold standard to asses skin damage, but it has significant limitations. Recently, several studies demonstrated the utility of skin high frequency ultrasound (US) as an alternative. Objectives: The aim of this study was to identify possible correlations between peripheral blood perfusion (BP) and ultrasound dermal thickness (US-DT) at level of hand and finger in SSc patients. Methods: Sixty-seven patients, satisfying the 2013 ACR/EULAR SSc criteria (mean age 64±9 SD years, mean disease duration 6±4 SD years) were enrolled. BP was measured as perfusion units (PU) by laser speckle contrast analysis (LASCA) at the level of dorsal region of hands, In a second time, different regions of interest (ROIs) were created at level of dorsum of the middle phalanx of 3rd finger and dorsum of hand bilaterally and the average BP was scored as perfusion units (PU), as previously reported. 1, 2 Both skin high frequency US and mRSS were used to evaluate DT at the above mentioned skin sites. 2 The same examinations were performed in 65 healthy subjects. Results: BP was negatively correlated with both US-DT (p=0.0005) and mRSS (p=0.007) in SSc patients at the finger sites, but not at the level of dorsum of the hands. In healthy subjects, there was no statistically significant correlation between BP and DT as evaluated by both US and mRSS at either skin sites. SSc patients showed a statistically significant lower BP at the finger sites than healthy subjects (p<0.0001). No statistically significant difference in BP values was observed between SSc and healthy subjects at the dorsum of hand. Conclusions: This study demonstrates a negative correlation between BP, as evaluated by LASCA and DT, as evaluated by both US and mRSS, in the 3rd finger of SSc patients. Additionally, the results confirm a reduced finger BP in SSc patients when compared to healthy subjects. Reference: [1] Ruaro B, et al. Microvasc Res. 2017;115:28–33. [2] Ruaro B, et al. Ann Rheum Dis. 2014;73:1181–85. [3] Cutolo M, et al. Best Pract Res Clin Rheumatol. 2016;30:670–87. Disclosure of Interest: None declared